The Practical Approach to Care Kit (PACK) guide: developing a clinical decision support tool to simplify, standardise and strengthen primary healthcare delivery. (17th October 2018) - Cornick, Ruth; Picken, Sandy; Wattrus, Camilla; Awotiwon, Ajibola; Carkeek, Emma; Hannington, Juliet; Spiller, Pearl; Bateman, Eric; Doherty, Tanya; Zwarenstein, Merrick; Fairall, Lara
Abstract : For the primary health worker in a low/middle-income country (LMIC) setting, delivering quality primary care is challenging. This is often complicated by clinical guidance that is out of date, inconsistent and informed by evidence from high-income countries that ignores LMIC resource constraints and burden of disease. The Knowledge Translation Unit (KTU) of the University of Cape Town Lung Institute has developed, implemented and evaluated a health systems intervention in South Africa, and localised it to Botswana, Nigeria, Ethiopia and Brazil, that simplifies and standardises the care delivered by primary health workers while strengthening the system in which they work. At the core of this intervention, called Practical Approach to Care Kit (PACK), is a clinical decision support tool, the PACK guide. This paper describes the development of the guide over an 18-year period and explains the design features that have addressed what the patient, the clinician and the health system need from clinical guidance, and have made it, in the words of a South African primary care nurse, 'A tool for every day for every patient'. It describes the lessons learnt during the development process that the KTU now applies to further development, maintenance and in-country localisation of the guide: develop clinical decision support in context first, involve local stakeholders in all stages, leverage others' evidence databases to remain up to date and ensure content development, updating and localisation articulate with implementation.